2020
DOI: 10.1002/jbio.202000090
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of microvessels in Optical Coherence Tomography angiography depends on angular orientation

Abstract: Optical Coherence Tomography angiography (OCTA) is a widespread tool for depthresolved imaging of chorioretinal vasculature with single microvessel resolution. To improve the clinical interpretation of OCTA, the conditions affecting visualization of microvessels must be defined. Here we inject a scattering plasma tracer (Intralipid) during OCTA imaging of the anesthetized rat eye. In the retina, we find that interlaminar (vertical) vessels that connect laminae have one-fourth to one-third the OCTA red blood ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Diving and surfacing vessels appear as dots in the 2D images, and are excluded from analysis by the use of minimum branch length filters. OCTA based on the intrinsic contrast mechanism of red blood cell flux was found to be severely negatively biased [18], which further validates only analysing vessels that have prominent in-plane projections.…”
Section: Discussionmentioning
confidence: 89%
“…Diving and surfacing vessels appear as dots in the 2D images, and are excluded from analysis by the use of minimum branch length filters. OCTA based on the intrinsic contrast mechanism of red blood cell flux was found to be severely negatively biased [18], which further validates only analysing vessels that have prominent in-plane projections.…”
Section: Discussionmentioning
confidence: 89%
“…As reported previously, the injection of Intralipid particles increases the intravascular intensity and angiogram signals as measured with OCT [ 11 ]. It has also been demonstrated that the vessels that run parallel to the beam axis exhibit the largest increases in scattering [ 29 ]. Due to the growth of NVs between the choroid and outer plexiform layer in a significantly vertical orientation, the visibility of NVs increased substantially following Intralipid injection and the boundaries of these vessels became much more apparent [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Intralipid can also be used as a biocompatible plasma tracer [ 11 ] and can be used to improve the OCT intensity, angiography, and Doppler signals [ 11 , 12 ]. It has further been shown that Intralipid 20% preferentially enhances the intravascular OCT signal in vessels which are parallel to the beam axis, thus improving their visibility [ 23 , 29 ]. Intralipid 20% has been chosen here for its ease of use, translational potential, and lipid makeup which is expected to be beneficial for retinal leakage imaging.…”
Section: Methodsmentioning
confidence: 99%
“… 42 , 43 The depth location of a scatterer within the sample is determined by the light path length of the photon that hits and be reflected by the scatterer. 11 Figure 3 shows the potential interactions of an incident photon when it enters the blood vessel and in the tissue. RBCs are the main scatters within blood vessels, whose interaction with incident photons results in dynamic contrast for OCTA imaging.…”
Section: Blood Vessel Tail Artifacts In Octamentioning
confidence: 99%
“…In principle, OCTA maps blood vessels using the signal dynamic contrast that signals blood vessels are changing over time due to the moving of RBCs, whereas signals from surrounding tissues are relative stable. 10 12 Thus, OCTA has the advantage of using an intrinsic contrast agent (i.e., RBCs) to differentiate blood vessels from surrounding tissues. With three dimensional (3D) and high-spatial resolution imaging ability of small vessels, OCTA has been widely used in a variety of studies, such as angiography of retina vessels in ophthalmology, 13 19 cerebrovascular perfusions in neuroscience, 20 , 21 cancer biology, 22 , 23 and skin diseases.…”
Section: Introductionmentioning
confidence: 99%